Impact Of Liquidity On Return On Assets Of Firms: Evidence From Nigeria (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
This study aims at examining the impact of liquidity on Return on Assets on 46 quoted firms listed on the Nigerian Stock Exchange from 2000-2009 . Liquidity and its management determine to a great extent the growth and profitability of a firm because inadequate or excess liquidity may be injurious to the smooth operations of the firm. This has become a source of concern for business managers as bank loans are becoming too expensive to maintain as a result of tightening of both the local and international financial market and the reluctance of the public to invest in the shares of companies sequel to the partial crash of the capital market. From the hypothesis test carried out, the result of the study showed that liquidity has a significant positive impact on Return on Assets (ROA), implying that a unit change in liquidity will result into a corresponding increase in ROA. It is concluded therefore that managers can increase profitability by putting in place good credit policy, short cash conversion cycle and an effective cash flow management procedures.